Analisis Faktor-Faktor Yang Mempengaruhi Tunggakan Pembayaran Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (PBB-P2) Pada Badan Pendapatan Daerah Kabupaten Sikka - Tobias Joni Temu; Magdalena Silawati Samosir; Nelti Fransiska (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This research aims to determine whether awareness factors, officer service, sanctions, level of knowledge and income level of taxpayers influence arrears in payment of Rural and Urban Land and Building Tax (PBB-P2) in Nita District, Sikka Regency. The population used in this research are employees of the Sikka Regency Regional Revenue Agency who specifically handle land and building taxes and the people of Sikka Regency who have 85,233 people in tax arrears for the last 2022. The sample used was 100 taxpayers who live in Sikka Regency and are registered with the Sikka Regency Regional Revenue Agency. The research results can be concluded that together the five independent variables are the awareness variable (X1), the tax officer service variable (X2), the sanctions variable (X3), the taxpayer knowledge level variable (X4), the taxpayer income level variable (X5). significant effect on PBB payment arrears (Y).